Operational criteria application does not change clinicians’ opinion on the diagnosis of mental disorder: a pre- and post-intervention validity study - Rocha Neto, Helio G.; Lessa, José Luiz Martins; Koiller, Luisa Mendez; Pereira, Amanda Machado; Gomes, Bianca Marques de Souza; Veloso Filho, Carlos Linhares; Casado Telleria, Carlos Henrique; Cavalcanti, Maria T.; Telles-Correia, Diogo (Frontiers in Psychiatry, 2024)
Objective: Our objective was to check if the ICD-10 operational criteria application changes non-operational, prototype-based diagnoses obtained in a real-life scenario. Methods: Psychiatry residents applied the diagnostic criteria of the ICD-10 as a "diagnostic test" to five outpatient patients they were already following who had a prototype-based diagnosis. Tests were used to ascertain whether changes in opinion were significant and if any of the diagnostic groups were more prone to change than others. The present paper is part of the study with UTN U1111-1260-1212. Results: Seventeen residents reviewed their last five case files, retrieving 85 diagnostic pairs of non-operational-based vs operational-based diagnoses. The Stuart-Maxwell test did not indicate a significant opinion change (X²=5.25, p=.39; Power=.94) besides 30% of diagnostic changes. Despite not being statistically significant, 20.2% of all evaluations resulted in a change that would affect treatment choices. Using ICD-10 operational criteria slightly increased the number of observed diagnoses, but probably without clinical relevance. None of the non-operational diagnoses have a higher tendency to change with operational criteria application (X²=11.6, p=.07). The female gender was associated with a higher diagnostic change tendency. Conclusion: Applying ICD-10 operational criteria as a diagnostic test does not induce a statistically significant diagnostic opinion change in residents and no diagnostic group seems more sensible to diagnostic change. Gender-related differences in diagnostic opinion changes might be evidence of sunk cost bias. Although not statistically significant, using operational criteria after diagnostic elaboration might help to deal with subjects without adequate treatment response.